1997
DOI: 10.1007/s004240050403
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of early aldosterone-induced RNAs identified in A6 kidney epithelia

Abstract: The early aldosterone-induced increase in Na reabsorption across tight epithelia is characterized by a transcription-dependent activation of epithelial Na channels (ENaC) and pumps (Na,K-ATPase). In order to contribute towards the identification of transcriptionally regulated mediators of this process, we first tested mRNAs of proteins previously suggested to be involved. Epithelia were treated for 1 h with 10(-6 )M aldosterone, a concentration which produces a maximal transport response and at which both mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 41 publications
9
98
1
1
Order By: Relevance
“…Therefore, the 4-h time point represents a point of transition between the early and the late responses in which the early and the late sets of genes are potentially coexisting. In favor of this hypothesis, the mRNAs accumulation kinetics of several recently identified early genes reveal (i.e., Sgk) that the mRNA levels remain significantly induced at least 6 h after hormone stimulation (10,11). Second, the major transcriptional effects of vasopressin presumably occur after several hours of hormonal treatment as it was demonstrated for ENaC, CFTR, AQP2, and Na,K-ATPase (3,13,14).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the 4-h time point represents a point of transition between the early and the late responses in which the early and the late sets of genes are potentially coexisting. In favor of this hypothesis, the mRNAs accumulation kinetics of several recently identified early genes reveal (i.e., Sgk) that the mRNA levels remain significantly induced at least 6 h after hormone stimulation (10,11). Second, the major transcriptional effects of vasopressin presumably occur after several hours of hormonal treatment as it was demonstrated for ENaC, CFTR, AQP2, and Na,K-ATPase (3,13,14).…”
Section: Resultsmentioning
confidence: 97%
“…The transcription-dependent aldosterone-signaling pathway (between receptor and membrane transport effectors) remains poorly understood. Only two gene products (Sgk and K-Ras) have recently been shown to be part of the pathway, but upstream and downstream mediators have not been identified at the molecular level (10,11).…”
mentioning
confidence: 99%
“…Mutating ␥Thr-623 into an Ala residue significantly decreased incorporation of 32 P into this subunit without affecting labeling by [ 35 S]methionine. In three different experiments using ϳ40 oocytes each, the mutation of Thr-623 lowered the 32 P/ 35 S ratio of the immunoprecipitated subunit by 47 Ϯ 15%. Thus, Thr-623 is one of the ␥ residues phosphorylated in the oocyte system.…”
Section: Resultsmentioning
confidence: 99%
“…Oocytes labeled with 32 P or 35 S were washed and homogenized in buffer A ϩ protease inhibitors, and membranes were isolated by centrifugation through a sucrose cushion. Membranes were solubilized in 1% Triton X-100 in buffer A and centrifuged for 5 min at 11,000 ϫ g to remove insoluble material.…”
Section: P]atpmentioning
confidence: 99%
“…3 The database search indicated that partial or incomplete sequences of LAT1 (E16, TA1 and ASUR4b) were already reported. 5,6,11 E16 and ASUR4b were identified to be up-regulated upon the mitogenic stimulation of lymphocytes and the stimulation of A6 epithelial cell line by aldosterone, respectively, 5,11 suggesting highly regulated nature of LAT1 gene expression. TA1 was identified as a tumor-associated sequence with the oncofetal pattern of expression in rat liver.…”
Section: Discussionmentioning
confidence: 99%